EXPLORING THE OPPORTUNITIES AND BARRIERS OF AI-DRIVEN TOOLS ON EFL STUDENTS’ ACADEMIC PERFORMANCE: PERSPECTIVES OF EFL UNIVERSITY STUDENTS - Happy Kusuma Wardani; Eva Nur Mazidah; Bariqotul Hidayah; Alimin Alimin; Zaimatus Sa’adah (Universitas Islam Ogan Komering Ilir Kayuagung, 2024)
Artificial Intelligence in education has revolutionized students' learning styles. This study explored EFL students' perspectives on how AI tools assist them in their academic performance. Eighty-two EFL students enrolled in the English Language Study Program at the University of Qomaruddin participated in the study. A survey method was adopted for this study through a series of questionnaires to collect feedback from the students. The result revealed that EFL students heavily rely on conversational AI tools like ChatGPT and machine translation. The study also highlighted the positive impact of AI on various aspects of language learning, including vocabulary acquisition, grammar proficiency, pronunciation practice, and academic writing refinement. However, the study identified concerns regarding the potential barriers to AI integration, such as overreliance on technology, the risk of replacing human teachers, and the need for enhanced digital literacy skills